Pemanfaatan Puding Daun Kelor Sebagai Upaya Pencegahan Stunting Di Desa Ringin Sari Kecamatan Suoh Kabupaten Lampung Barat - al Arif, M. Yasin; Anggi Fitriani; Bayu Anshor Mursalin; Ghufron Hidayat; Happy Sreshi Aska Kenda; Lisa Virliana; Muhammad Rizki Ramadhan; Reni Latifah; Witri Leviana; Zahrani Amrina (Swadaya: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a failure in children's growth and development. Stunting is caused by chronic malnutrition that occurs within 1000 days of life. Malnutrition among children under five is one of the main problems of the Indonesian nation because it has an impact on the low quality of human resources. Improved nutrition is needed to avoid these problems for children aged 6-24 months. Moringa leaves (Moringa oleifera) have nutrients that can help improve children's nutritional status. The content of macro minerals such as calcium, potassium and phosphorus plays an important role in the growth of bones and teeth, activating nerves and the brain, as well as maintaining heart health. Method: This Community Service Activity uses a demonstration method which aims to promote the method of processing Moringa leaves. We know that Moringa leaves are rich in nutritional content which supports nutritional development, especially for stunted children as additional food at posyandu. Results: During the training, participants participated in the activities enthusiastically.  This was proven by several questions asked by participants regarding how to make Moringa leaf pudding.